Modified (2/1-k) output gain ?uk DC-to-DC converter circuit for renewable power applications - Ozsoy E.; Padmanaban S.; Oluwafemi A.W.; Ramachandaramurthy V.K.; Sutikno T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; Global warming; MATLAB; Power electronics; Timing circuits; Analytical analysis; DC-to-DC converters; Global warming and climate changes; Perspective views; Renewable energy applications; Switched-capacitor topology; Voltage conversion ratio; Voltage-lift technique; DC-DC converters